Deforestación y sus consecuencias en la biodiversidad para el desarrollo del turismo de naturaleza del cantón Montalvo, Provincia de Los Ríos - Coloma Benítez, Jeffrey Vitali (2025)
This research work addresses the problem of deforestation and its consequences on biodiversity and nature tourism in the Montalvo canton, province of Los Ríos, with the main objective of determining the impact on biodiversity as a consequence of deforestation and its impact on the development of nature tourism in the Montalvo canton, province of Los Ríos, with the purpose of understanding how this problem negatively affects the environment and tourism development in the area. It is proposed to expose relevant bibliographic evidence on the variables that make up the problem and that allow understanding the origin of deforestation in the area and analyze the effects it has on the existing biodiversity in the canton, using an exploratory methodology with a qualitative approach for the collection of truthful and relevant information to demonstrate the opinion of local residents through data collection techniques such as surveys, focus groups and interviews and with the analysis of the results to raise the appropriate conclusions and recommendations. It is proposed as a possible result that deforestation has had a negative impact on biodiversity, affecting the development of nature tourism in the canton of Montalvo, Los Ríos province, which will allow the application of appropriate corrective measures by the relevant authorities to amend the damage caused to biodiversity, as well as to enhance the sustainability of nature tourism through the implementation of conservation strategies that generate balance and environmental protection.